A study on the Relationship of the Lachnidae, Chaitophoridae, Thelaxidae, Eriosomatidae, Adelgidae, Phylloxeridae and their Aphidiid Parasites in (Central) Europe (Homoptera: Aphidoidea; Hymenoptera: Aphidiidae). - Starý, Petr (Contributions to Entomology = Beiträge zur Entomologie, 1963)
A review of aphidiid parasites of aphid families Lachnidae, Chaitophoridae, Thelaxidae, Eriosomatidae, Adelgidac and Phylloxeridae in (Central) Europe and ecological characteristics of parasites are given.